SELEKSI IN VITRO KALUS KEDELAI (Glycine max L.) HASIL INDUKSI MUTASI MENGGUNAKAN ETIL METAN SULFONAT TOLERAN KEKERINGAN DAN ALUMINIUM - Gustian Gustian; Muhammad Rafli Ibrahim; Benni Satria; Ryan Budi Setiawan; Silvia Permata Sari (Fakultas Pertanian, Universitas Janabadra, 2024)
Soybean (Glycine max L.) is a type of nutritious food crop because soybean seeds have high protein amino acid content. Increasing domestic production for soybean self-sufficiency needs to be done by expanding the planting area. The objective of this research is to examine the effect of ethyl methane sulfonate concentration and obtain soybean plants tolerant to drought and aluminum stress through in vitro selection. This research was conducted from November 2023 to January 2024 at the Tissue Culture Laboratory, Faculty of Agriculture, Andalas University. The research was arranged in a Completely Randomized Design consisting of 12 treatment levels of the combination of concentrations of abiotic selection agents PEG 4000 and AlCl3 induced by EMS mutation and 12 treatment levels of the combination of concentrations of abiotic selection agents PEG 4000 and AlCl3 not induced by EMS mutation with 3 replications. Data analysis was performed using independent sample t-test at a significance level of 5% and interpreted descriptively. The results showed that mutation induction using ethyl methane sulfonate (EMS) did not produce soybean somatic embryo mutants tolerant to drought and aluminum stress. Meanwhile, results from non-mutated callus produced somatic embryos suspected to be potential putative somaclonal candidates tolerant to drought and aluminum after double in vitro selection using 10% PEG 4000 and 150 ppm AlCl3 selection agents.